Education Using Lecture and Leaflet on Knowledge and Attitude of Women on Visual Inspection of Acetic Acid - Suriani Agreini Sagoba; Zairin Noor; Meitria Syahadatina Noor; Husaini Husaini; Harapan Parlindungan Ringoringo (Lambung Mangkurat, 2022)
Awareness of women in conducting Visual Inspection of Acetic Acid (VIA) as an early screening for cervical cancer is still quite low, therefore efforts are needed to increase it by education for women with lecture method or leaflet. The purpose of this paper is to determine the effect of providing health education with lecture and leaflet methods on knowledge and attitudes of women about VIA. There are 10 research articles related to knowledge and attitudes using the lecture method and leaflets about VIA obtained through Google Scholar, Garuda Portal, and Research Gate. Based on the results of research articles study, there was an effect of providing education with the lecture method on knowledge of 1.45; [95% Cl: 0.240-2.670, Z=2.349, p=0.018834]; and there was an effect on attitude of 1.04; [95% Cl: 0.170-1.920, Z=2.311, p=0.019775]. There was an effect of providing education with leaflets on knowledge of 1.71; [95% Cl: 0.580-2.840, Z=2.957, p=0.003103]; and there was no effect on the attitude of 0.58; [95% Cl: 0.580-2.840, Z=2.957, p=0.003103]. The conclusions are there is an effect of providing health education with the lecture method on knowledge and there is an effect of providing health education with the leaflet method on knowledge.